Neuroscience - Purves, Dale. (Editor); Augustine, George J. (Editor); Fitzpatrick, David. (Editor); LaMantia, Antony-Samuel. (Editor); McNamara, James O.(Editor); Williams, S. Mark. (Editor) (Sunderland, Mass Sinauer Associates, Publishers, 2004)
A comprehensive textbook created primarily for medical and premedical students. Text boxes, new and revised, highlight topics of special interest relevant to the chapter topics; these include discussions of the major neurological diseases, research methods, and the relevant animal models. Also includes additional neuroanatomical content, including two appendices: (1) The Brainstem and Cranial Nerves, and (2) Vascular Supply, the Meninges, and Ventricles. Sylvius for Neuroscience: Visual Glossary of Human Neuroanatomy (CD included with every copy) is an interactive reference guide to the human nervous system
The Organization of the Nervous System; PART I: NEURAL SIGNALING: Electrical Signals of Nerve Cells; Voltage dependent; Membrane Permeability Channels and Transporters; Synaptic Transmission; Neurotransmitters, Receptors ;and their Effects; Intracellular Signal Transduction; The Somatic Sensory System; Pain; PART II: Vision: The Eye; Central Visual Pathways; The Auditory System; The Vestibular System; PART III: MOVEMENT AND ITS CENTRAL CONTROL: Lower Motor Neuron Circuits and Motor Control; Upper Motor Neuron Control of the Brainstem and Spinal Cord; Modulation of Movement by the Basal Ganglia; Modulation of Movement by the Cerebellum; Eye Movements and Sensory Motor Integration; The Visceral Motor System; PART IV: THE CHANGING BRAIN: Early Brain Development; Construction of Neural Circuits; Modification of Brain Circuits as a Result of Experience; Plasticity of Mature Synapses and Circuits; PART V: COMPLEX BRAIN FUNCTIONS: The Association; Cortices; Language and Speech; Sleep and Wakefulness; Emotions; Sex, Sexuality, and the Brain; Memory; APPENDIX A: THE BRAINSTEM AND CRANIAL NERVES; APPENDIX B: VASCULAR SUPPLY, THE MENINGES, AND THE VENTRICLES; Glossary; Illustration; Credits; Index
Includes bibliographical references and index.
Keywords: Nervous System Physiology; Neurochemistry